Environmental performance of biological nutrient removal processes from a life cycle perspective - Ontiveros, Guillermo Alejandro (2013)
The goal of the present study is to assess different alternatives for a wastewater treatment plant module with capacity to remove nutrients biologically, taking into account present Argentine regulations for effluent discharge. A computational modeling tool (GPS-X) was employed to simulate the behavior of the different alternatives, and Life Cycle Assessment was applied to quantify the environmental impact. A 2000 m3/d municipal wastewater flow was used to carry out the simulations, the annual flow was utilized as functional units and the main topics analyzed were energy efficiency, land use, eutrophication reduction and biosolid reuse. Biogas and biosolid generation was evaluated as a good opportunity to generate a cleaner process. This study highlights the fact that nutrient removal processes significantly improve the quality of effluent and biosolids and reduces energy consumption.